Can Enhanced Autophagy Be Associated with Human Longevity? Serum Levels of the Autophagy Biomarker Beclin-1 Are Increased in Healthy Centenarians - YILMAZ, YUSUF (MARY ANN LIEBERT, INC, 2014)
Autophagy is a major clearance mechanism that degrades organelles and large protein aggregates to maintain cell survival and protein homeostasis. Although induction of autophagy can promote longevity in experimental models, the question as to whether increased basal levels of autophagy can be associated with human longevity remains open. In this pilot study, we investigated the association between serum concentrations of beclin-1, a key regulator of autophagy, and human exceptional longevity (EL). Serum beclin-1 was measured in three study groups: 79 healthy centenarians (39 males, aged 100-104 years); 178 non-diabetic patients who had experienced an acute myocardial infarction at a young age (101 males, 28-39 years); and 180 age- and sex-matched healthy young volunteers (103 males, 27-39 years) using an enzyme-linked immunosorbent assay. Healthy centenarians had significantly higher beclin-1 levels (2.2 +/- 0.8 ng/mL) compared with both young patients with myocardial infarction (1.5 +/- 0.7 ng/mL; p<0.001) and healthy controls (1.4 +/- 0.9 ng/mL; p<0.001), whereas no significant difference was observed between the two groups of young subjects. The multivariate-adjusted odds ratio for having serum beclin-1 levels >1.5 ng/mL (i.e., 75th percentile of the young controls' levels) was 3.4 (95% confidence interval 1.8-5.7; p<0.001) for healthy centenarians. Our preliminary data suggest that elevated basal levels of autophagy as reflected by high serum beclin-1 levels may be a biomarker of healthy human EL.
Keywords: LIFE-SPAN EXTENSION; CALORIC RESTRICTION; MECHANISMS; DISEASE; GENES